Analisis retorika tiga tokoh masyarakat dengan gaya bahasa berbeda: Anies Baswedan, Najwa Shihab, dan Susi Pudjiastuti - Wirayuda, Muhammad Reza (Maliki Interdisciplinary Journal, 2025)
Rhetoric plays a crucial role in shaping a public figure’s image and social influence. This study aims to analyze the rhetorical styles of three Indonesian public figures—Anies Baswedan, Najwa Shihab, and Susi Pudjiastuti—each representing distinct linguistic and communicative characteristics. The research employs a rhetorical discourse analysis approach with a comparative technique applied to speeches, interviews, and public statements of the three figures. The findings reveal that Anies Baswedan demonstrates an academic-logical rhetoric grounded in logos and ethos; Najwa Shihab combines critical-dialogical rhetoric balancing ethos and pathos; while Susi Pudjiastuti adopts a populist-expressive rhetoric emphasizing pathos. Collectively, they represent the pluralistic nature of Indonesian public rhetoric that integrates rationality, morality, and emotional appeal. This study contributes to a deeper understanding of public communication strategies and enhances rhetorical literacy development in Indonesia.